What are the needs of people with dementia in acute hospital settings, and what interventions are made to meet these needs? A systematic integrative review of the literature - Janne Røsvik; Anne Marie Mork Rokstad (BMC, 2020)
Abstract Background Research aiming to improve the hospital experience for patients with dementia and their informal carers is strongly recommended. The present review aimed to describe the research on interventions to meet the needs of people with dementia in acute hospital settings regarding physical environment, organization of care, and staff knowledge of dementia and competence in person-centred care. An integrative review design was applied. We searched for studies in PubMed, Ovid Medline, Cinahl, Embase, Swemed+, and Cochrane databases using the Mixed Methods Appraisal Tool (MMAT) for quality evaluation. Twenty-seven articles were included, describing the perspectives of people with dementia, informal carers, and professional carers. The MMAT score ranged from two to four. Twelve studies described needs and experiences, mostly using a qualitative design. Common themes and results were synthesized. The studies identified a need to enhance staff competence regarding dementia and person-centred care. Fifteen studies described interventions: two were qualitative; three used mixed method, and 10 were quantitative, of which two were randomized controlled trials and eight were observational studies. Five types of interventions were identified. Three types could positively impact staff knowledge about dementia and person-centred care. One type was experienced as positive regarding organisation of care for patients with dementia. None of the intervention studies found evidence for effects on the identified needs regarding physical environment. Conclusion The included studies suggest that staff need more knowledge regarding dementia and person-centred dementia care and that training interventions implemented to enhance staff competence had promising results. However, there is a need for research on the needs of patients with dementia in acute hospital settings regarding physical environment and effect of design elements. There is also a scarcity of intervention studies focusing on the effect of models of care that support the psychosocial needs of patients with dementia.